Leadership in Environmental Education: The Role of Madrasah Principals in Madrasah - M. Aditiya Imansyah; Eti Hadiati; Ahmad Fauzan; Oki Dermawan (Indonesian Journal of Education and Social Studies, 2025)
This study aims to describe and analyze the leadership of madrasa principals in realizing environmentally aware madrasas in State Elementary Madrasas (MIN) throughout West Lampung, including their roles in mobilizing, directing, guiding, fostering, encouraging, and providing assistance to all members of the madrasa community. This research method uses a descriptive qualitative approach, with the research sites located at MIN 1 and MIN 2 in West Lampung. Data collection used observation, interviews, and documentation. Interviews were conducted with the madrasa principal, the Adiwiyata head, staff, and classroom teachers. Data analysis used data reduction, data presentation, and conclusion drawing. Data validity techniques included source triangulation and technical triangulation. The study shows how Madrasah Principals in West Lampung lead environmentally conscious initiatives at MIN. 1) They mobilise the community through motivation, role models, and forming an Adiwiyata team. 2) They integrate environmental planning with the curriculum and instil Islamic values. 3) They offer guidance through training and innovation, fostering an eco-conscious culture. 4) They promote environmental responsibility through religious and environmental activities. 5) They motivate with awards for creativity and moral growth. 6) They support green infrastructure and community partnerships.